Longitudinal Outcomes in the 2014 Acute Flaccid Paralysis Cluster in Canada: A Nationwide Study. (March 2017) - Yea, Carmen; Bitnun, Ari; Robinson, Joan; Mineyko, Aleksandra; Barton, Michelle; Mah, Jean K.; Vajsar, Jiri; Richardson, Susan; Licht, Christoph; Brophy, Jason; Crone, Megan; Desai, Shalini; et al.
We describe the presenting features and long-term outcome of an unusual cluster of pediatric acute flaccid paralysis cases that occurred in Canada during the 2014 enterovirus D68 outbreak. Children (n = 25; median age 7.8 years) presenting to Canadian centers between July 1 and October 31, 2014, and who met diagnostic criteria for acute flaccid paralysis were evaluated retrospectively. The predominant presenting features included prodromal respiratory illness (n = 22), cerebrospinal fluid lymphocytic pleocytosis (n = 18), pain in neck/back (n = 14) and extremities (n = 10), bowel/bladder dysfunction (n = 9), focal central gray matter lesions found in all regions of the spinal cord within the cohort (n = 16), brain stem lesions (n = 8), and bulbar symptoms (n = 5). Enterovirus D68 was detectable in nasopharyngeal specimens (n = 7) but not in cerebrospinal fluid. Acute therapies (corticosteroids, intravenous immunoglobulins, plasmapheresis) were well tolerated with few side effects. Fourteen of 16 patients who were followed beyond 12 months post onset had neurologic deficits but showed ongoing clinical improvement and motor recovery.